Effects of 8-week alkaline diet and aerobic exercise on body composition, aerobic performance, and lipid profiles in sedentary women - Yalcinkaya, Nehir; Isik, Ozkan; Beyleroglu, Malik; Erdogdu, Dogan; Cicek, Guner; Novak, Dario (Frontiers in Nutrition, 2024)
Background Diet composition can affect systemic pH and acid–base regulation, which may in turn influence exercise performance. Purpose It was aimed to determine the effects of the alkaline diet and 8 weeks of aerobic exercises on body composition, aerobic performance, and blood lipid profiles in sedentary women. Methods Thirty-two sedentary women participated in the study voluntarily. The research was designed with a true-experimental design and the participants were divided into four different groups as the control group, aerobic exercise group, alkaline diet group, and alkaline diet + aerobic exercise group. The body compositions, aerobic exercise performances, and lipid profiles of sedentary women were measured as pre-test and post-test. In the analysis of the obtained data, One-Way ANOVA with Bonferroni post hoc test was used. Results It was observed that the alkaline diet consumed with 8 weeks of aerobic exercises caused a 5.17% decrease in BMI and an increase of 42.07 and 37.62% in VO2max and aerobic test durations, respectively (p < 0.05). In addition, when lipid profiles were examined, it was determined that there was no statistically significant difference in HDL-C levels (p > 0.05). Despite that, there were statistically significant differences in TG and LDL-C levels (p < 0.05). According to this result, it was determined that there was a decrease in TG and LDL-C levels by 37.61 and 20.24%, respectively. Conclusion An alkaline diet consumed with 8 weeks of aerobic exercises in sedentary women has positive effects on improving body composition, aerobic exercise performances, and TG and LDL-C levels.